PWE-061 Homozyogosity in the ApoE4 polymorphism is associated with dysphagic symptoms in an otherwise healthy elderly population. (28th May 2012) - Mentz, H; Pendleton, N; Hamdy, S
Abstract : Introduction: Apolipoprotein E (ApoE) is thought to be the most common genetic risk factor for Alzheimer's disease and has a number of polymorphisms. While the E2 allele is proposed to play a protective role, it E4 allele is said to increase the risk of cognitive decline. We therefore hypothesised that the presence of ApoE4 would be predictive of dysphagia symptoms. Methods: 800 members of a genetically well characterised community dwelling elderly cohort received the Sydney oropharyngeal dysphagia questionnaire via mail. 1 Cognitive function was also measured using the Telephone Interview of Cognitive Status and mood with the Geriatric Depression Score (GDS). ApoE4/2 allele status was then correlated with dysphagia symptoms. Results: Completed questionnaire response rate was 79% (23.5% men, 76.5% women; mean age 81±5 years; range 69–98 years). Possession of one or more of the ApoE4 and 2 alleles was found in 23.5% and 16% respectively. Swallowing score was significantly related to GDS (CC 0.133, p<0.001**) and Age (CC 0.107, p<0.007**). While dysphagia was not significantly associated with possession of single E4 or E2 alleles, ApoE4 homozygosity was associated with significantly higher swallowing scores compared to all other allele combinations (p=0.033). Conclusion: We have shown a novel relationship between self reported dysphagic symptoms and ApoE genotype in community dwelling older adults. The presence of ApoE4 homozygostiy appears to associate with dysphagia symptoms but requires replication in independent larger cohorts. Competing interests: None declared. Reference: 1. Wallace KL, Middleton S, Cook IJ. Development and validation of a self-report symptom inventory to assess the severity of oral-pharyngeal dysphagia. Gastroenterology 2000;118 :678–87.